Prevalence of obesity in diabetic and non-diabetic population - Akholkar, Pankaj J.; Gandhi, Amita A. (International Journal of Research in Medical Sciences, 2017)
Background: In the last two decades there have been marked secular, increases in the prevalence of obesity in the majority of countries worldwide. More than 1.1 billion individuals meet current definitions for overweight or obesity which puts them at increased risk for number of chronic diseases including cardiovascular diseases (CVD) and type-2 diabetes. Its objective is to study anthropometric (measurements) in diabetic and non-diabetic population by taking Indian indicators (Modified ATP III criteria for South Asian population) and WHO criteria for WHR for determining obesity. The study also aimed at finding out whether Waist Circumference (WC) is sufficient enough to measure obesity instead of Body Mass Index (BMI) to detect obesity in Diabetic patients, when we use Modified ATP III criteria South Asians. Methods: Study was undertaken at urban based Medical College and hospital situated at Sola, in Ahmedabad, Gujarat, India. A total of 100 patients attending the medical outdoor patient department were categorized in two sub groups: 1. diabetic, 2. non-diabetic, Obesity was defined by using BMI and waist circumference criteria for South Asian phenotype in modified ATP- lll and NCEP criteria and WHO criteria for WHR. Results: Prevalence of obesity using BMI was found to be 71 %( n=71) as most of these patients were obese by the above mentioned criteria. Statistically significant increase in prevalence of obesity in diabetics is noted when Indian indicators were used. This was true for both the indicators WC as well as WHR which noted 83% and 81% more obesity respectively. Further in our study, waist circumference (83%) is found to be marginally better indicator for diagnosis of obesity than BMI (71%). Conclusions: In the present study, obesity was positively related to anthropometric variables such as Body Mass Index (BMI) and WC and WHR .Our study also suggests that only a simple measurement of waist circumference can suffice detection of obesity in diabetics. Our study also highlights the alarming increase in the prevalence of obesity developing countries, such as India due to effect of urbanization and changing lifestyle.